2022
DOI: 10.1071/cp21436
|View full text |Cite
|
Sign up to set email alerts
|

Iron fortification of food crops through nanofertilisation

Abstract: Micronutrient deficiencies are a significant cause of malnutrition worldwide, particularly in developing countries, affecting nearly 1.8 billion people worldwide. Agriculture is the primary source of nutrients for humans, but the increasing population and reducing arable lands areas are putting the agricultural sector under pressure, particularly in developing and less developed countries, and calls for intensive farming to increase crop yield to overcome food and nutrients deficiency challenges. Iron is an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Many scientists are now working to develop effective and sustainable approaches to agronomic biofortification. Chugh et al (2022) reviewed the current use of iron (Fe) nano-fertilisers for Fe biofortification; they also identified the challenges that must be addressed to optimise nano-fertilisation for sustainable agriculture. For wheat grown in acidic soil, Jalal et al (2022a) compared foliar rates of ZnO nanoparticles for increasing grain zinc (Zn) concentration and grain yield.…”
Section: Mineral Biofortificationmentioning
confidence: 99%
“…Many scientists are now working to develop effective and sustainable approaches to agronomic biofortification. Chugh et al (2022) reviewed the current use of iron (Fe) nano-fertilisers for Fe biofortification; they also identified the challenges that must be addressed to optimise nano-fertilisation for sustainable agriculture. For wheat grown in acidic soil, Jalal et al (2022a) compared foliar rates of ZnO nanoparticles for increasing grain zinc (Zn) concentration and grain yield.…”
Section: Mineral Biofortificationmentioning
confidence: 99%
“…Agronomic biofortification programs have demonstrated the potential to improve pasture sustainability by increasing the nutritional quality of forage crops [21][22][23]. This improvement not only benefits the livestock consuming the fortified feed but also contributes to enhancing overall soil health and ecosystem sustainability [24,25]. It represents a promising way to improve pasture sustainability by enhancing the nutritional quality of forage crops like Trifolium subterraneum, thereby promoting more resilient and nutrient-rich pasture ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…27 Fe-chelate nanofertilizers, carbon-coated Fe NPs, Fe 3 O 4 , and Fe 2 O 3 NPs have been tested as Fe fertilizers on wheat plants. 28 The results of some studies demonstrated that Fe-NPs improved wheat yield, and protein, carbohydrate, and amino acid content in wheat grains. [29][30][31] Furthermore, CoFe 2 O 4 NPs have attracted attention for agricultural applications, due to their low toxicity and environmental compatibility.…”
Section: Introductionmentioning
confidence: 99%